Loop Diuretics Have Anxiolytic Effects in Rat Models of Conditioned Anxiety - Krystal, Andrew D.; Sutherland, Janice; Hochman, Daryl W. (PLOS ONE, 2012)
A number of antiepileptic medications that modulate GABAA mediated synaptic transmission are anxiolytic. The loop diuretics furosemide (Lasix) and bumetanide (Bumex) are thought to have antiepileptic properties. These drugs also modulate GABAA mediated signalling through their antagonism of cation-chloride cotransporters. Given that loop diuretics may act as antiepileptic drugs that modulate GABAergic signalling, we sought to investigate whether they also mediate anxiolytic effects. Here we report the first investigation of the anxiolytic effects of these drugs in rat models of anxiety. Furosemide and bumetanide were tested in adult rats for their anxiolytic effects using four standard anxiety models: 1) contextual fear conditioning; 2) fear-potentiated startle; 3) elevated plus maze, and 4) open-field test. Furosemide and bumetanide significantly reduced conditioned anxiety in the contextual fear-conditioning and fear-potentiated startle models. At the tested doses, neither compound had significant anxiolytic effects on unconditioned anxiety in the elevated plus maze and open-field test models. These observations suggest that loop diuretics elicit significant anxiolytic effects in rat models of conditioned anxiety. Since loop diuretics are antagonists of the NKCC1 and KCC2 cotransporters, these results implicate the cation-chloride cotransport system as possible molecular mechanism involved in anxiety, and as novel pharmacological target for the development of anxiolytics. In view of these findings, and since furosemide and bumetanide are safe and well tolerated drugs, the clinical potential of loop diuretics for treating some types of anxiety disorders deserves further investigation.